IMPLEMENTASI PENDIDIKAN KARAKTER MELALUI EKSTRAKURIKULER SENI TARI DI SD N 2 BUGISAN PRAMBANAN KLATEN - Prisma Prisma; Endang Hangestiningsih (TRIHAYU: Jurnal Pendidikan Ke-SD-an, 2019)
This study aims to describe the implementation of character education through extracurricular dance activities at Bugisan Prambanan Klaten 2 state elementary school. This research is a qualitative descriptive study. The data source of the study consisted of principals, dance teachers, class III-V teachers, and students of class III-V. The technique of collecting data is done by interviews, observation, and documentation. Check data validity using source, technique, and time triangulation. The data analysis technique used is the Milles and Huberman model where researchers conduct data collection, data reduction, data presentation, and conclusion drawing.